2020
DOI: 10.1016/j.ajoc.2020.100981
|View full text |Cite
|
Sign up to set email alerts
|

Short-term outcomes following treatment of recalcitrant cystoid macular edema secondary to radiation maculopathy using intravitreal brolucizumab

Abstract: Purpose To assess the efficacy of intravitreal brolucizumab (Beovu®, Novartis Pharmaceuticals) in a case of recalcitrant cystoid macular edema associated with radiation maculopathy secondary to retinoblastoma which was suboptimally responsive to other intravitreal anti-vascular endothelial growth factor (VEGF) therapies. Observations A 42-year old patient with a history of radiation maculopathy complicated by cystoid macular edema after chemoreduction treatment and radi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 11 publications
0
4
0
Order By: Relevance
“…A single injection of the drug led to visual gain and remarkable macular thickness reduction with minimal residual fluid that lasted for 8 weeks. 77 …”
Section: Real-world Clinical Datamentioning
confidence: 99%
See 2 more Smart Citations
“…A single injection of the drug led to visual gain and remarkable macular thickness reduction with minimal residual fluid that lasted for 8 weeks. 77 …”
Section: Real-world Clinical Datamentioning
confidence: 99%
“…A single injection of the drug led to visual gain and remarkable macular thickness reduction with minimal residual fluid that lasted for 8 weeks. 77 Murray et al studied the off-label use of intravitreal brolucizumab as a rescue therapy in a series of eyes with vision compromising macular oedema (MO) secondary to different ocular conditions, which had not responded to prior repetitive anti-VEGF or steroid treatment. 78 Analysis showed significant reduction of MO as well as marked BCVA improvement for all study participants following brolucizumab administration.…”
Section: Retinal Vein Occlusion (Rvo) and Other Ocular Disordersmentioning
confidence: 99%
See 1 more Smart Citation
“…Thus, prior treatment with anti-VEGF agents seems to have a better outcome than using IVTA in treatment-naive eyes. Isolated case reports on the use of aflibercept 90 and brolucizumab 91 in recalcitrant edema have also been recently published. Intravitreal dexamethasone implant is another effective treatment option, although Seibel et al demonstrated no difference in VA or central foveal thickness when comparing it with intravitreal bevacizumab and IVTA.…”
Section: Treatmentmentioning
confidence: 99%